The Relationship between Corporate Social Responsibility and Employee Satisfaction with the Business Performance of Beverage Companies in West Java - Sidrotun Naim (Westscience Press, 2023)
This research aims to evaluate the connection between corporate social responsibility (CSR), the level of satisfaction experienced by employees, and the level of success experienced by the organization as a whole in a beverage manufacturing company located in West Java. Data from around two hundred workers in the beverage industry were gathered through the application of quantitative research methodologies. The study's findings indicate a good connection between CSR, employee satisfaction, and the performance of businesses. According to the findings of this study, corporate social responsibility (CSR) and business performance are connected in a way that is mediated through employee happiness. These findings have significant repercussions for businesses that want to boost their financial performance by increasing their commitment to CSR and the satisfaction of their workforce.